Nyai Mela: Perintis Pesantren Perempuan di Depok - Siti Hadiyanti Dini Islamiati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Starting from concerns about the loss of Nyai Mela's history, due to the lack of literacy about her struggles in the field of education, this research was conducted. Researchers will examine Nyai Mela's work in educating women in the city of Depok and its surroundings. The method used is a qualitative method, with data collection techniques in the form of observation, documentation, and predominantly through interviews. The results of the research are that Nyai Mela not only provides Islamic religious education for women, but also teaches various skills. Later, his education and teaching was institutionalized in the form of a girls' boarding school, the results of which are felt to this day by women in the city of Depok